(untitled) (Educational Dimension, 2022)
Information technology is becoming an increasingly important part of the lives of today’s youth, opening up numerous opportunities for its application in various fields of public practice. The statistics presented in the article on the increasing demand for gaming IT industry products update the search for ways to incorporate gamification components in the educational space in order to optimize the process of professional development of a competitive specialist. The article considers the incorporation of gamification into the educational process of higher education institutions in order to develop stress resistance in individuals as a factor in selecting constructive strategies for overcoming life crises in young people. The concept of gamification is investigated using scientific research analysis. The benefits of gamification in the educational and psychocorrectional processes are established. The use of simulator games with augmented and virtual reality elements in the process of developing constructive coping strategies of individual behavior in uncertain situations and overcoming life crises is supported. The article describes the experience of interdisciplinary research at Bogdan Khmelnytsky Melitopol State Pedagogical University’s STEAM-laboratory, Laboratory of Psychophysiological Research, and Laboratory of Health Psychology. The paper describes in detail the step-by-step empirical study on the incorporation of gamification components as well as augmented and virtual reality technologies into a comprehensive training program aimed at developing resilience, emotional stability, and as a predictor of constructive strategies for overcoming life crises in young people. The implementation of the experience is described in the stages of ascertaining and shaping the study. According to the findings, implementing a psycho-correctional program with gamification elements aided in increasing the individual’s emotional stability and stress resistance. Representatives of the experimental group, who received active training using gamification elements and AR/VR technologies, demonstrated significant differences in the choice of constructive strategies for overcoming life crises when compared to the control group, which did not receive training.